Normative Consciousness Displacement in Artificial Intelligence Mediated Legal Interpretation Systems and Its Consequences for Human Judicial Sovereignty - Yohanna YR Watofa; Marsel Mickael Fenanlabir; Henk M. Sombuk (Civiliza Publishing, 2026)
This study examines the phenomenon of shifting normative awareness in artificial intelligence-based legal interpretation systems and its implications for judges' sovereignty in modern judicial practice. The research is motivated by the increasing use of artificial intelligence in the legal interpretation process which raises problems related to the reduction of judges' autonomy, ethical responsibility, and humanitarian dimension in law enforcement. This study aims to analyze the influence of artificial intelligence systems on the legal interpretation process and identify its consequences on the existence of human judicial sovereignty. The research uses a normative juridical approach with a qualitative analysis method. Data was obtained through a document study of 45 legal sources consisting of laws and regulations, court decisions, scientific articles, policy reports, and international regulatory frameworks related to artificial intelligence and legal technology. Data analysis was carried out using content analysis techniques and comparative legal interpretation. The results show that artificial intelligence systems tend to place computational consistency and predictive efficiency above contextual, moral, and sociological dimensions in legal interpretation, thus contributing to the weakening of human normative awareness in judicial decision-making. This study concludes that the integration of artificial intelligence in the legal system requires strengthening ethical governance and human supervision mechanisms to maintain judicial sovereignty, legal legitimacy, and substantive justice in the digital era.